High carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material and preparation method thereof
By adding amino and hydroxyl-containing biomass to the biomass-based hard carbon material, and carrying out cross-linking reactions and specific heat treatment processes, the problem of low carbon yield of biomass-based hard carbon materials is solved, and high carbon yield is achieved It combines excellent sodium storage performance, improves the performance and economy of sodium ion batteries.
Patent Information
- Application Number
- CN202410307813.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-03-18
AI Technical Summary
The carbon yield of biomass-based hard carbon materials is generally low, which limits production capacity and increases preparation costs, and is difficult to maintain excellent sodium storage performance at the same time.
By adding hydroxyl-containing biomass B to amino-containing biomass A and cross-linking reaction occurs with crosslinking agent, combined with low-temperature pretreatment and high-temperature carbonization process, the carbon yield is significantly improved and the microstructure of hard carbon materials is optimized. .
It achieves high carbon yield (25% to 50%) and excellent sodium storage performance, which improves the electrochemical sodium storage performance and cycle stability of sodium ion batteries, while reducing preparation costs and improving production capacity.
Smart Images

Figure CN118026145B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy secondary battery material processing, and specifically relates to a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material and a preparation method thereof. Background Art
[0002] As a common secondary battery, lithium-ion batteries have been widely used in the field of energy storage due to their high safety, high energy density and excellent cycle stability. However, with the scarcity of lithium resources and the rise in prices, lithium-ion batteries cannot meet the huge demand of electric vehicles (EV) and hybrid electric vehicles (HEV). Therefore, the search for alternatives to lithium-ion batteries has attracted widespread attention from researchers in the energy field. Sodium-ion batteries have attracted widespread attention due to their similar working principles to lithium-ion batteries, low cost and abundant resources. However, compared with lithium ions, sodium ions have a larger radius ( vs ), and the intercalation of sodium ions into graphite is not thermodynamically feasible. Therefore, finding suitable anode materials remains a challenge in sodium-ion battery research.
[0003] Hard carbon has a large carbon layer spacing (0.37-0.42nm) and randomly oriented pseudographite nanodomains. It has a unique pore structure, which is conducive to the embedding / de-embedding of sodium ions. After embedding sodium, the volume expansion is small, the safety is good, and the structure is stable. Therefore, hard carbon is considered to be the most promising negative electrode material for sodium ion batteries. At present, the precursor raw materials used for hard carbon are mainly biomass, resin-based and petroleum-based. Among them, the hard carbon prepared by resin-based has obvious performance advantages, but the cost is expensive and the industrialization is difficult; petroleum-based precursors are low in cost, easy to obtain raw materials, and cost-effective, but the performance is general, and there are environmental pollution problems; while biomass has a unique microstructure, the raw materials are extensive, sustainable and low in price, the preparation process is simple, and it shows a high specific capacity and excellent rate and cycle performance. It has both high performance and low cost advantages and is the current mainstream research direction. However, the carbon yield of biomass-based hard carbon is generally low, generally between 10 and 20wt.%, so that the production capacity is severely limited and the preparation cost increases. Therefore, it is particularly important to improve the carbon yield of biomass-based hard carbon materials while maintaining their excellent sodium storage performance.
[0004] At present, the yield can be improved and a stable hard carbon structure can be obtained by pretreating the biomass precursor. For example, the use of a combination of a soft carbon precursor and a hard carbon precursor can increase the final hard carbon yield. However, the addition of the soft carbon precursor also reduces the sodium storage capacity of the final carbon material. In general, there are few studies on improving the carbon yield of biomass-based hard carbon materials. Therefore, it is of great significance to develop a preparation method that can significantly improve the carbon yield of biomass-based hard carbon materials while maintaining the excellent sodium storage performance of biomass-based hard carbon materials. Summary of the invention
[0005] The purpose of the present invention is to provide a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material and a preparation method thereof which have both high carbon yield and excellent sodium storage performance. By selecting suitable precursors and pretreatment process methods, low-cost and high-efficiency preparation of high carbon yield nitrogen-doped hard carbon materials can be achieved to overcome the disadvantage that the carbon yield of existing biomass-based hard carbon is generally low.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material is provided. Hydroxyl-containing biomass B is added to amino-containing biomass A, and a cross-linking reaction is carried out together with a cross-linking agent, and then carbonization is performed to obtain the high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material. The carbon yield of the hard carbon negative electrode material is 25% to 50%, the interlayer spacing is 0.37 to 0.39 nm, and the nitrogen doping amount is 1wt.% to 5wt.%.
[0008] The method for preparing the high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material comprises the following steps:
[0009] (1) physically mixing the amino-containing biomass A, the hydroxyl-containing biomass B and the cross-linking agent to obtain a uniform mixture;
[0010] (2) transferring the mixture to a homogeneous reaction vessel for cross-linking reaction at a temperature of 60 to 150° C. for a time of 1 to 10 hours to obtain a cross-linked mixture C with a stable structure;
[0011] (3) Under an inert atmosphere, the cross-linked mixture C is subjected to a low-temperature pretreatment, the temperature is increased to 200 to 600° C. at a heating rate of 1 to 5° C. / min, the temperature is maintained for 1 to 6 hours, and the mixture is cooled to room temperature to obtain an intermediate product;
[0012] (4) Under an inert atmosphere, the intermediate product is subjected to high-temperature carbonization, the temperature is raised to 900-1500°C at a rate of 1-10°C / min and the temperature is kept for 0.5-8h. After cooling to room temperature, a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material is obtained.
[0013] Furthermore, in the step (1), the amino-containing biomass A is at least one of chitosan, chitosan oligosaccharide, carboxymethyl chitosan, carboxymethyl chitosan oligosaccharide, glucosamine, mannosamine, and galactosamine.
[0014] Furthermore, in step (1), the hydroxyl-containing biomass B is at least one of starch, cellulose, lignin, sucrose and glucose.
[0015] Furthermore, in step (1), the crosslinking agent is one of maleic anhydride, phthalic anhydride, benzoic anhydride, acetic anhydride, ethylpropionic anhydride, succinic anhydride, acetic anhydride, propionic anhydride, butyric anhydride, maleic anhydride, trimellitic anhydride, and 3,4,9,10-perylenetetracarboxylic anhydride.
[0016] Furthermore, in the step (1), the mass ratio of the amino-containing biomass A, the hydroxyl-containing biomass B, and the cross-linking agent is 4-12:4-12:1-4.
[0017] Furthermore, in step (3), the inert atmosphere is one of nitrogen and argon.
[0018] Furthermore, in step (4), the inert atmosphere is one of nitrogen and argon.
[0019] The application of the high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material is that the hard carbon negative electrode material is contained in a negative electrode sheet, and the negative electrode sheet is contained in a sodium ion half cell or a sodium ion battery.
[0020] The design idea of the present invention is:
[0021] The present invention significantly enhances the cross-linking effect of the biomass precursor and the structural stability during the heat treatment process by reacting the amino groups in the biomass molecules rich in amino groups with the cross-linking agent, avoiding the direct pyrolysis of the precursor into small molecules, thereby significantly improving the carbon yield. In addition, using the biomass rich in amino groups as a precursor, a nitrogen-doped hard carbon negative electrode material can be obtained, and nitrogen doping can not only enhance the conductivity of the hard carbon negative electrode material, but also adjust the microstructure of the hard carbon negative electrode material and increase the sodium storage active site, thereby further improving the sodium storage performance of the sodium ion battery. Under the premise of not changing the hard carbon yield, hydroxyl-containing biomass is added to the amino-containing biomass, and a cross-linking reaction occurs with the cross-linking agent to adjust the cross-linking effect of the biomass molecules, optimize the microstructure (carbon layer interlayer spacing, defects, pore structure, etc.) of the obtained hard carbon material, and further improve the first coulomb efficiency, capacity and cycle stability of the hard carbon material.
[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0023] 1. In the present invention, biomass A contains abundant amino groups, which are easy to undergo amidation reaction with a cross-linking agent, which can significantly enhance the cross-linking effect of the biomass precursor and the structural stability during the heat treatment process, and significantly improve the carbon yield. In addition, the abundant amino groups contained in biomass A also help to obtain nitrogen-doped hard carbon materials. Nitrogen doping can not only enhance the conductivity of hard carbon materials, but also adjust the microstructure of hard carbon, increase sodium storage active sites, and further improve the sodium storage performance of sodium ion batteries.
[0024] 2. Without changing the hard carbon yield, hydroxyl-containing biomass B is added to amino-containing biomass A to undergo a cross-linking reaction with a cross-linking agent to adjust the cross-linking effect of the biomass molecules and optimize the microstructure of the obtained hard carbon material (carbon layer interlayer spacing, defects, pore structure, etc.), thereby further improving the first coulombic efficiency, capacity and cycle stability of the hard carbon material.
[0025] 3. The hard carbon material for the negative electrode of the sodium ion battery of the present invention has the advantages of high carbon yield, high specific capacity, good rate performance and stable cycle performance, simple preparation process, wide source of raw materials and low cost. Since the carbon yield is significantly improved, the cost is significantly reduced, the production capacity is also significantly improved, the product has good technical and economic performance, and it is easy to realize large-scale industrial production, which is of great significance for the commercial application of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD graph of the high carbon yield nitrogen-doped hard carbon negative electrode material of Example 1 of the present invention. In the graph, the abscissa 2Theta is the diffraction angle (degree), and the ordinate Intensity is the relative intensity (au).
[0027] Figure 2 The infrared curves of the hard carbon negative electrode materials of Example 1 and Comparative Example 1 of the present invention are shown in FIG. 1 . In the figure, the abscissa Wavenumber represents the wave number (cm -1 ), the vertical axis Transmittance represents transmittance (au).
[0028] Figure 3 The thermogravimetric curves of the hard carbon negative electrode materials of Example 1 and Comparative Examples 1 and 2 of the present invention are shown in FIG. 1 , where the abscissa Temperature represents temperature (° C.) and the ordinate Mass represents weight loss (%).
[0029] Figure 4 The cyclic voltammetry curve of the high carbon yield nitrogen-doped hard carbon negative electrode material of Example 1 of the present invention. In the figure, the horizontal axis Potential represents the potential (V vs. Na + / Na), the vertical axis Current represents the current (mA), and the cyclic voltammetry curves of the first three cycles (1st, 2nd, and 3rd) are basically overlapped.
[0030] Figure 5 The charge and discharge curve of the high carbon yield nitrogen-doped hard carbon negative electrode material of Example 1 of the present invention is shown in FIG. 1. In the figure, the abscissa Specific capacity represents the specific capacity (mAh g -1 ), the vertical axis Potential represents the potential (V vs.Na + / Na), the cyclic voltammetry curves of the 2nd and 3rd cycles basically overlap.
[0031] Figure 6 The battery cycle performance comparison diagram of the hard carbon negative electrode material of Example 1 of the present invention and Comparative Example 1. In the figure, the horizontal axis Cycle number represents the number of cycles, and the vertical axis Specific capacity represents the specific capacity (mAh g -1 ).
[0032] Figure 7 The figure is a comparison chart of the battery rate performance of the hard carbon negative electrode materials of Example 1 of the present invention and Comparative Example 1. In the figure, the abscissa Cycle number represents the number of cycles, and the ordinate Specific capacity represents the specific capacity (mAh g -1 ).
[0033] Figure 8 This is a comparison diagram of the electrochemical impedance spectra of the hard carbon negative electrode materials of Example 1 of the present invention and Comparative Example 1. In the figure, the abscissa Z' represents the real part of the impedance (ohm), and the ordinate Z" represents the imaginary part of the impedance (ohm). DETAILED DESCRIPTION
[0034] In the specific implementation process, the present invention proposes a preparation method of a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material, comprising the following steps: (1) physically mixing amino-containing biomass A, hydroxyl-containing biomass B and a cross-linking agent to obtain a uniformly mixed mixture; (2) transferring the mixture to a homogeneous reactor, performing a cross-linking reaction at a certain temperature, and obtaining a structurally stable cross-linked mixture C; (3) performing low-temperature pretreatment and high-temperature carbonization on the cross-linked mixture C to obtain a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material.
[0035] According to another aspect of the present invention, a negative electrode sheet is provided, and the hard carbon negative electrode material of the present invention is applied to a sodium ion battery, and its material performance advantages are brought into play in combination with the characteristics of the sodium ion battery.
[0036] The negative electrode sheet is obtained by coating a mixed slurry containing the aforementioned high carbon yield nitrogen-doped hard carbon negative electrode material or the hard carbon negative electrode material prepared by the aforementioned method, a conductive agent, and a binder on a metal foil, preferably an aluminum foil, treating it at high temperature, and slicing it. In the mixed slurry, the mass ratio of the hard carbon negative electrode material, the conductive agent, and the binder is 7-9:0.5-1.5:0.5-1.5.
[0037] Specifically, the hard carbon negative electrode material, conductive agent (Super P) and binder (sodium carboxymethyl cellulose CMC) are evenly ground in a mass ratio of 8:1:1, and a small amount of deionized water is added to make a slurry. The slurry is applied to copper foil or aluminum foil with a coater, and then kept at 100°C in a vacuum drying oven for 24 hours. Finally, the dried electrode sheet is cut into electrode sheets with a diameter of 12 mm with a slicer.
[0038] According to another aspect of the present invention, there is provided a sodium ion half-cell or a sodium ion battery, comprising the above-mentioned negative electrode sheet.
[0039] The present invention is further described in detail below in conjunction with test examples and specific implementation methods. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention.
[0040] Example 1
[0041] Preparation of high carbon yield nitrogen-doped hard carbon anode material sample 1#
[0042] 5g starch, 5g chitosan and 1g maleic anhydride were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a blast drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a cross-linked mixture with a stable structure; the cross-linked mixture powder was placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product was ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a high-yield nitrogen-doped hard carbon negative electrode material for a negative electrode of a sodium ion battery, recorded as sample 1#. In this embodiment, the nitrogen doping amount of the hard carbon negative electrode material is 3.1wt.%, and the carbon layer spacing is 0.384nm.
[0043] Taking the high carbon yield nitrogen-doped hard carbon negative electrode material of the present invention as an example, its crystal structure is obtained by X-ray diffractometer testing. Figure 1 As shown, the XRD pattern of Example 1#, from Figure 1It can be seen that the peaks of the (002) crystal plane and (100) crystal plane of amorphous carbon appear at diffraction angles of about 23° and 44°, respectively, and no other impurity peaks are observed, indicating that the obtained material is a hard carbon material.
[0044] The sample after the starch and chitosan mixed cross-linking treatment in Example 1 and the sample of the starch and chitosan mixed without cross-linking in Comparative Example 1 were subjected to infrared testing, and the infrared curve is shown in FIG. Figure 2 ,from Figure 2 It can be seen that the sample after starch and chitosan mixed cross-linking treatment in Example 1 has a -1 There is an obvious absorption peak of esterification group or amidation group at 3350cm -1 The peak intensities of the OH and NH stretching vibration peaks at 240 nm were significantly weakened after cross-linking treatment, indicating that sufficient cross-linking had occurred inside the biomass precursor.
[0045] The samples after starch and chitosan crosslinking treatment in Example 1, the samples after starch and chitosan crosslinking treatment in Comparative Example 1, the samples after starch and maleic anhydride crosslinking treatment in Comparative Example 2, and the samples after chitosan and maleic anhydride crosslinking treatment in Comparative Example 3 were subjected to thermogravimetric test. The thermogravimetric curve is shown in FIG. Figure 3 .from Figure 3 It can be seen that the thermogravimetric curves of the sample after the cross-linking treatment of chitosan and maleic anhydride mixed in Comparative Example 3 and the sample after the cross-linking treatment of starch and chitosan mixed in Example 1 are similar, and they no longer lose weight after 700°C. At 900°C, the carbon yield of the former is 36.57%, and the carbon yield of the latter is still 37.58wt.%. It can be seen that the addition of starch did not reduce the carbon yield of Example 1, but slightly increased it. The carbon yield of the sample mixed with starch and chitosan in Comparative Example 1 without cross-linking is only 17.54wt.% at 900°C, and when the temperature continues to rise from 900°C, it still has a tendency to continue to lose weight. This fully illustrates that the cross-linking treatment of the present invention can effectively improve the structural stability and carbon yield of the final hard carbon negative electrode material. The carbon yield of the sample after mixed cross-linking treatment of starch and maleic anhydride in Comparative Example 2 at 900°C is very close to that of Comparative Example 1, which is only 18.37wt.%. When the temperature continues to rise from 900°C, it also has a trend of continuing to lose weight, indicating that the addition of chitosan rich in amino groups is the key to improving the structural stability and carbon yield of the final hard carbon negative electrode material.
[0046] The hard carbon negative electrode material prepared by the present invention is used as the negative electrode active material of the sodium ion battery, assembled into a sodium ion button battery, and the performance of the button battery is tested. Figure 4As shown in the cyclic voltammetry curve of the first three cycles of the sample in Example 1#, it can be clearly observed that there is a pair of redox peaks around 0.1V. This pair of peaks corresponds to the platform area in the charge-discharge curve, which is caused by the embedding / de-embedding of sodium ions between carbon layers and the filling / ejection of sodium ions into micropores. The overlap rate of the cyclic voltammetry curve is very high, indicating that the reversibility of the material is very good. Figure 5 As shown in the figure, the charge-discharge curves of the first three cycles of the sample in Example 1 at a current density of 0.03A / g. It can be clearly observed in the figure that the charge-discharge curves of hard carbon contain obvious platform capacity and slope capacity. The first discharge capacity and charge capacity are 395mAh / g and 351mAh / g respectively, and the first coulombic efficiency (ICE) is as high as 88.93%. Figure 6-Figure 7 As shown, the cycle performance test was carried out under the condition of current density of 0.03A / g. Figure 6 It can be seen that the cycle performance of Example 1# sample is stable, and the discharge capacity is still 342 mAh / g after 40 cycles, while the discharge capacity of Comparative Example 1# sample is only 278 mAh / g after 40 cycles. Figure 7 It can be seen that the rate performance of Example 1# sample is excellent. After charging and discharging at different current densities of 30 to 1200 mA / g, the discharge capacity at a current density of 30 mA / g is still as high as 343 mAh / g, while the discharge capacity of Comparative Example 1# sample at different current densities of 30 to 1200 mA / g is lower than that of Example 1# sample. Figure 8 The electrochemical impedance spectra of the hard carbon negative electrode material of Example 1 and Comparative Example 1 are compared. Figure 8 It can be seen that the electronic and ionic conduction of Example 1# sample are better than that of Comparative Example 1# sample. The above sodium ion battery performance shows that the prepared high-yield nitrogen-doped hard carbon negative electrode material has very excellent electrochemical sodium storage performance and is a sodium ion battery negative electrode material with great potential application value.
[0047] Example 2
[0048] Preparation of high carbon yield nitrogen-doped hard carbon anode material 2# sample
[0049] 5g starch, 2.5g chitosan and 1g maleic anhydride were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a forced air drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a cross-linked mixture with a stable structure; the cross-linked mixture powder was placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product was ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a high-yield nitrogen-doped hard carbon negative electrode material for a negative electrode of a sodium ion battery, recorded as sample 2#. In this embodiment, the nitrogen doping amount of the hard carbon negative electrode material is 1.4wt.%, and the carbon layer spacing is 0.374nm.
[0050] The high-yield nitrogen-doped hard carbon negative electrode material sample 2# obtained in this example is used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity is 303 mAh / g at a current density of 0.03 A / g, and the first coulombic efficiency is 81%.
[0051] Example 3
[0052] Preparation of high carbon yield nitrogen-doped hard carbon anode material 3# sample
[0053] 2.5g starch, 5g chitosan and 1g maleic anhydride were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a blast drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a cross-linked mixture with a stable structure; the cross-linked mixture powder was placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product was ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a high-yield nitrogen-doped hard carbon negative electrode material for a negative electrode of a sodium ion battery, recorded as sample 3#. In this embodiment, the nitrogen doping amount of the hard carbon negative electrode material is 4.2wt.%, and the carbon layer spacing is 0.389nm.
[0054] The high-yield nitrogen-doped hard carbon negative electrode material sample 3# obtained in this example is used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity is 328 mAh / g at a current density of 0.03 A / g, and the first coulombic efficiency is 85%.
[0055] Example 4
[0056] Preparation of 4# sample of nitrogen-doped hard carbon anode material with high carbon yield
[0057] 5g starch, 5g chitosan and 1g phthalic anhydride were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a blast drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a cross-linked mixture with a stable structure; the cross-linked mixture powder was placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product was ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a high-yield nitrogen-doped hard carbon negative electrode material for a negative electrode of a sodium ion battery, recorded as sample 4#. In this embodiment, the nitrogen doping amount of the hard carbon negative electrode material is 2.3wt.%, and the carbon layer spacing is 0.379nm.
[0058] The high-yield nitrogen-doped hard carbon negative electrode material 4# sample obtained in this example was used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity was 335 mAh / g at a current density of 0.03 A / g, and the first coulombic efficiency was 88%.
[0059] Example 5
[0060] Preparation of 5# sample of nitrogen-doped hard carbon anode material with high carbon yield
[0061] 5g starch, 5g chitosan and 1g maleic anhydride were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a blast drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a cross-linked mixture with a stable structure; the cross-linked mixture powder was placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product was ground into powder, placed in a tube furnace, heated to 1200°C at a heating rate of 5°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a high-yield nitrogen-doped hard carbon negative electrode material for a negative electrode of a sodium ion battery, recorded as sample 5#. In this embodiment, the nitrogen doping amount of the hard carbon negative electrode material is 3.3wt.%, and the carbon layer spacing is 0.388nm.
[0062] The high-yield nitrogen-doped hard carbon negative electrode material 5# sample obtained in this example was used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity was 316 mAh / g at a current density of 0.03 A / g, and the first coulombic efficiency was 84%.
[0063] Example 6
[0064] Preparation of high carbon yield nitrogen-doped hard carbon anode material 6# sample
[0065] 5g starch, 5g chitosan and 1g maleic anhydride were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a blast drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a cross-linked mixture with a stable structure; the cross-linked mixture powder was placed in a tube furnace, heated to 600°C at a heating rate of 2°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a low-temperature pretreatment product; the low-temperature pretreatment product was ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min for 2h under an argon atmosphere, and cooled to room temperature with the furnace to obtain a high-yield nitrogen-doped hard carbon negative electrode material for a negative electrode of a sodium ion battery, recorded as sample 6#. In this embodiment, the nitrogen doping amount of the hard carbon negative electrode material is 2.0wt.%, and the carbon layer spacing is 0.376nm.
[0066] The high-yield nitrogen-doped hard carbon negative electrode material sample 6# obtained in this example is used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity is 329 mAh / g at a current density of 0.03 A / g, and the first coulombic efficiency is 87%.
[0067] Comparative Example 1
[0068] Hard Carbon Anode Material Comparative Example 1# Sample Preparation
[0069] 5g of starch and 5g of chitosan were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a forced air drying oven, treated at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a mixture; the mixture powder was placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product was ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a nitrogen-doped hard carbon negative electrode material for a negative electrode of a sodium ion battery, recorded as comparative example 1# sample. In this comparative example, the nitrogen doping amount of the hard carbon negative electrode material is 1.2wt.%, and the carbon layer spacing is 0.372nm.
[0070] The hard carbon negative electrode material comparative example 1# sample obtained in this comparative example is used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity is 288mAh / g at a current density of 0.03A / g, and the first coulombic efficiency is 88%.
[0071] Comparative Example 2
[0072] Preparation of hard carbon negative electrode material comparative example 2# sample
[0073] 5g of starch and 1g of maleic anhydride are physically mixed to obtain a uniform mixture; the mixture is transferred to a homogeneous reaction kettle, transferred to a blast drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder is ground into powder with a mortar to obtain a cross-linked compound of starch; the cross-linked compound powder of starch is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product is ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a hard carbon material for the negative electrode of a sodium ion battery, which is recorded as Comparative Example 2# sample. In this comparative example, the nitrogen doping amount of the hard carbon negative electrode material is 0wt.%, and the carbon layer spacing is 0.369nm.
[0074] The hard carbon negative electrode material comparative example 2# sample obtained in this comparative example is used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity is 307mAh / g at a current density of 0.03A / g, and the first coulombic efficiency is 83%.
[0075] Comparative Example 3
[0076] Preparation of hard carbon negative electrode material comparative example 3# sample
[0077] 5g of chitosan and 1g of maleic anhydride were physically mixed to obtain a uniform mixture; the mixture was transferred to a homogeneous reaction kettle, transferred to a blast drying oven, reacted at 90°C for 2h, and after naturally cooling to room temperature, the powder was ground into powder with a mortar to obtain a cross-linked compound of starch; the cross-linked compound powder of starch was placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a low-temperature pretreated product; the low-temperature pretreated product was ground into powder, placed in a tube furnace, heated to 1400°C at a heating rate of 5°C / min under an argon atmosphere for 2h, and cooled to room temperature with the furnace to obtain a hard carbon material for the negative electrode of a sodium ion battery, which was recorded as comparative example 2# sample. In this comparative example, the nitrogen doping amount of the hard carbon negative electrode material is 3.9wt.%, and the carbon layer spacing is 0.393nm.
[0078] The hard carbon negative electrode material comparative example 3# sample obtained in this comparative example is used as the negative electrode active material of the sodium ion battery and assembled into a sodium ion button battery. The first reversible specific capacity is 319 mAh / g at a current density of 0.03 A / g, and the first coulombic efficiency is 79%.
[0079] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the above disclosed technical content to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material, characterized in that: A hydroxyl-containing biomass B is added to an amino-containing biomass A, and a cross-linking reaction is carried out with a cross-linking agent, and then a high-carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material is obtained by low-temperature pretreatment and high-temperature carbonization; the carbon yield of the hard carbon negative electrode material is 25% to 50%, the interlayer spacing is 0.37 to 0.39 nm, and the nitrogen doping amount is 1 wt.% to 5 wt.%; The method for preparing the high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material comprises the following steps: (1) physically mixing the amino-containing biomass A, the hydroxyl-containing biomass B, and the cross-linking agent to obtain a uniform mixture; (2) transferring the mixture to a homogeneous reactor for cross-linking reaction, wherein the temperature of the cross-linking reaction is 90 to 150° C., and the time of the cross-linking reaction is 2 to 10 hours, wherein the amino groups in the biomass A undergo amidation reaction with the cross-linking agent to obtain a cross-linked mixture C with a stable structure; (3) Under an inert atmosphere, the cross-linked mixture C is subjected to a low-temperature pretreatment, the temperature is increased to 400-600° C. at a heating rate of 1-5° C. / min, the temperature is maintained for 1-6 hours, and the mixture is cooled to room temperature to obtain an intermediate product; (4) In an inert atmosphere, the intermediate product is subjected to high-temperature carbonization, the temperature is raised to 900-1500° C. at a rate of 1-10° C. / min and the temperature is kept for 0.5-8 hours, and after cooling to room temperature, a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material is obtained; In the step (1), the cross-linking agent is maleic anhydride or phthalic anhydride; In the step (1), the mass ratio of the amino-containing biomass A, the hydroxyl-containing biomass B, and the cross-linking agent is 4-12:4-12:1-4.
2. The method for preparing a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In the step (1), the amino-containing biomass A is at least one of chitosan, chitosan oligosaccharide, carboxymethyl chitosan, carboxymethyl chitosan oligosaccharide, glucosamine, mannosamine, and galactosamine.
3. The method for preparing a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In the step (1), the hydroxyl-containing biomass B is at least one of starch, cellulose, lignin, sucrose and glucose.
4. The method for preparing a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In the step (3), the inert atmosphere is one of nitrogen and argon.
5. The method for preparing a high carbon yield nitrogen-doped sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In the step (4), the inert atmosphere is one of nitrogen and argon.
Citation Information
Patent Citations
Sodium-ion battery hard carbon negative electrode material prepared by biomass-based crosslinking and application of sodium-ion battery hard carbon negative electrode material
CN117623270A